Disaster Preparedness Training Center - Wong, Lewis Jr. C. (College of Architecture, University of the Philippines Diliman, 2018)
With the Philippines being a disaster-prone country, it is necessary that people are well-equipped with the knowledge and skills needed in preparing and responding to disasters. As such, the aim of this thesis is to design a facility that will house different trainings and lectures that are relevant to addressing this issue that are currently being conducted in various areas in the country. The project is to be funded by the government and its main client will be the Office of Civil Defense - Training Division. RA 10121, also known as "The Philippine Disaster Risk Reduction and Management Act of 2010" serves as the main thrust for the project as it calls for the need to establish a DRRM Training Institute where the private and public individuals learn more about DRRM and its surrounding issues. It will also serve as the source for research and publication of DRRM training materials. The site chosen for the project is where the Ayala TBI currently stands which is located along CP Garcia and Katipunan Avenue near UP Diliman in Quezon City. The reason for this is that it is in close proximity to residential buildings where trainers and trainees can stay in the duration of their trainings and to institutional buildings. The site's location makes it less prone from natural hazards experienced in the country such as floods and earthquakes.